Public Attitudes toward Official Bilingualism in Canada: Making Sense of Regional and Subregional Variation. Issue 4 (2nd October 2018) - Dufresne, Yannick; Ruderman, Nick
ABSTRACT: Pierre Trudeau's vision of Canada's cultural policy was situated within a bilingual framework. Canada, so conceived, has "no official culture" and two official languages. Nearly 50 years later, debates regarding the effects and broader significance of this policy combination persist as illustrated by the recent debate about Supreme Court judges. Yet, Canadians' attitudes about bilingualism have received relatively little scholarly attention. This paper probes the structure and recent evolution of public attitudes toward the general idea of official bilingualism using the Survey on Official Languages (2003) and the Canadian Election Studies (1997–2011). It goes on to investigate regional differences in public support for bilingual Supreme Court judges using a large-scale survey conducted by Vox Pop Labs in 2015 ( n = 291, 577). The combination of these data sources offers new insights into the contextual and individual-level determinants of regional differences in public attitudes toward bilingualism policy in Canada.